Influence of Temperature on the Development of Flower Buds and Fruit Ripening of Some Introduced Pear Varieties in Swaida Province (Damascus University Journal of agriculture sciences, 2021)
This research was carried out at the General Commission for Scientific Agricultural Research- Pome and Grapevine Division in Sweida province during 2016-2017 on three introduced pears varieties: Santamaria, Abyvetal, Anjou, in order to study the phenological stages of flower buds, and determine the influence of temperature on the development of them, and on fruits ripening. The results showed that the study area provides the needs of the studied varieties of chilling hours, and the difference in the number of chilling hours between the two years caused a difference in the dates of the beginning of flower buds burst, as well the high temperatures in February above biological zero accelerated the onset of flower buds. And it was found that the variance of temperatures causes a difference in the duration of phenological stages of flower buds, and these stages are inversely related to the temperature. The differences were significant among the varieties for the number of days after full bloom in the two seasons of study, and Anjou, Abyvetal, and Santamaria varieties needed 168, 154, and 136 days respectively, while the differences were not significant between the two seasons for all varieties due to no difference in temperature during fruit development period. The current research shows that the development of flower buds of the studied varieties  in the high altitude areas is closely related to the temperature conditions during the periods between each stage and the other.
Keywords: Pear; Flower buds; Phenological stages; Chillin